Functional brain alterations during self-reference processing in adolescents with sexual abuse-related post-traumatic stress disorder: A preliminary report. Issue 1 (2nd January 2017) - Dégeilh, Fanny; Viard, Armelle; Guénolé, Fabian; Gaubert, Malo; Egler, Pierre-Jean; Egret, Stéphanie; Gerardin, Priscille; Baleyte, Jean-Marc; Eustache, Francis; Dayana, Jacques; Guillery-Girard, Bérengère
ABSTRACT: We proposed to explore the functional brain changes during a self-reference processing (SRP) task in adolescents with sexual abuse-related post-traumatic stress disorder ( N = 10), compared with healthy adolescents ( N = 10). While patients showed no behavioral disturbances in (SRP), they exhibited changes in activity and connectivity in regions involved in emotional regulation (amygdala and dorsal prefrontal cortex) and semantic memory (temporal and ventrolateral prefrontal regions). These preliminary results suggest that these alterations may have an effect on self-esteem which may contribute to a possible retention and impairment of symptoms in adulthood.